An examination of the anxiolytic effects of exercise for people with anxiety and stress-related disorders: A meta-analysis. (March 2017) - Stubbs, Brendon; Vancampfort, Davy; Rosenbaum, Simon; Firth, Joseph; Cosco, Theodore; Veronese, Nicola; Salum, Giovanni A.; Schuch, Felipe B.
Abstract: The literature regarding exercise for people with established anxiety disorders is equivocal. To address this issue, we conducted a systematic review and meta-analysis investigating the benefits of exercise compared to usual treatment or control conditions in people with an anxiety and/or stress-related disorders. Major electronic databases were searched from inception until December/2015 and a random effect meta-analysis conducted. Altogether, six randomized control trials (RCTs) including 262 adults (exercise n=132, 34.74 [9.6] years; control n=130, 37.34 [10.0] years) were included. Exercise significantly decreased anxiety symptoms more than control conditions, with a moderate effect size (Standardized Mean Difference=−0.582, 95%CI −1.0 to −0.76, p=0.02). Our data suggest that exercise is effective in improving anxiety symptoms in people with a current diagnosis of anxiety and/ or stress-related disorders. Taken together with the wider benefits of exercise on wellbeing and cardiovascular health, these findings reinforce exercise as an important treatment option in people with anxiety/stress disorders. Highlights: Previous literature regarding the benefits of exercise for anxiety/ stress disorders is equivocal. Our data suggest that exercise is more effective than control at reducing anxiety symptoms. Given its wider health benefits, exercise should be considered a strategy to improve the health of this population.